Kinematic study of overconstrained linkages and design of reconfigurable mechanisms - Song, Chao-Yang. (2014)
This dissertation explores the possibilities to design reconfigurable mechanisms using the kinematic and geometric properties of existing overconstrained linkages with revolute joints. Despite the large number of overconstrained linkages reported in literatures, there lacks of a comprehensive study into the relationship among them, which limits the understanding of the overconstrained linkages and their potential applications.